Peran Kepuasan Kerja Memediasi Pengaruh Kompensasi terhadap Loyalitas: (Studi pada Karyawan Divisi Mekanik Autotama Bali) - Ni Nyoman Widianingsih; I Gusti Ayu Dewi Adnyani (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Loyalty is a manifestation that is reflected in the attitudes and behavior of employees. Employees who have loyalty will seriously carry out their work and always correct the mistakes they make in their work. This research aims to analyze the role of job satisfaction in mediating the influence of compensation on loyalty. This research was conducted at Autotama Bali. The population in this study were 43 employees of the Autotama Bali mechanical division. The sampling technique used in this research was a saturated sampling technique with 43 respondents as the sample. Data collection methods in this research used questionnaires and interviews. The analysis techniques used are path analysis, classical assumption test, and Sobel test. The results of this research show that rewards have a positive and significant effect on loyalty, rewards have a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on loyalty, job satisfaction mediates the effect of rewards on loyalty. The implication of this research is to provide additional evidence of justice theory and its relationship with research variables, and become a consideration for Autotama Bali in increasing employee loyalty.